The Sabah factors in the Malaysian nation-state construction: identity confusion, nationalism and migrants - Han, Huhe (Penerbit Universiti Kebangsaan Malaysia, 2025)
The rise of Sabahan nationalism in Malaysia has been linked to concerns about the loss of autonomy and uneven distribution of resources within the federation. Sabah was granted a high degree of autonomy when it joined the Malaysian Federation under the 1963 Malaysia Agreement (MA63), but this has been eroded over time by federal government statutes and constitutional amendments. This has led to discontent among the people of Sabah and Sarawak, particularly over the distribution of royalties from the oil and gas industry. The lack of investment in infrastructure and public services in Sabah has also contributed to this discontent, fueling calls for greater autonomy and fairer treatment within the federation. The paper also analyzes the complex relationship between locals and migrants in the Malaysian state of Sabah: immigrants’ economic contributions to the local economy, the challenges faced by the local community, and the negative perceptions of locals towards immigrant events. The paper concludes with a discussion of the controversy surrounding the federal government’s naturalization of a large number of Muslim migrants as citizens through the IC Project (Identity Card Project) and its impact on Sabah’s demographic and political landscape. The paper argues that the complex dynamics between Sabah’s diverse population, foreign Muslim migrants and its federal government remains an important issue in the construction of the nation-state in contemporary Malaysia.